Answer:
![u(x,t) = (g(x))/(sin((kb)))sin((ky)) Fsinh{(kx)}](https://img.qammunity.org/2020/formulas/mathematics/high-school/1ssmlcw4geja36p9khikh79b1zx2iiy3qw.png)
Explanation:
The Laplace's equation in rectangular coordinates is:
![(\partial^2 u)/(\partial x^2) +(\partial^2 u)/(\partial y^2) = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/5ao5i3ik40cbzl9d3znpoq64r206vk29nn.png)
For the solution, we assume that u can be write as
![u(x,y) = X(x)Y(y)](https://img.qammunity.org/2020/formulas/mathematics/high-school/kz68tbfhctbjnvximavgvnnjea5690tnom.png)
Replace
![Y(y)(d^2X)/(dx^2) +X(x)(d^2Y)/(dy^2) =0](https://img.qammunity.org/2020/formulas/mathematics/high-school/l018ybenji0zbdejak8pc1kqucgy901ojg.png)
Divide
![X(x) Y(y)](https://img.qammunity.org/2020/formulas/mathematics/high-school/nyne7wm8r4dd0h3jso4qhn9q036jhw2145.png)
![(1)/(X(x))(d^2X)/(dx^2)= -(1)/(Y(y))(d^2Y)/(dy^2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/l4sadr5wxge4nt5rbmaqcgiohu54i2e12h.png)
The only way that this can be true, is that every term is the same constant, so we say that
![(1)/(X(x))(d^2X)/(dx^2) = -(1)/(Y(y))(d^2Y)/(dy^2) = k^2](https://img.qammunity.org/2020/formulas/mathematics/high-school/x3lokdgs3i1rfylcnc42a0rpw7tmhwcbv5.png)
With
a constant.
Now, we solve every part. For
![X(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/w5fx1ihwq47jf7p80nf72wcr7isw99lfm3.png)
![(d^2X)/(dx^2) = k^2X(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/z5wpdm19butxw71x3vgq69dsdpowrqy3sa.png)
The solution is:
![X(x) = Ee^(kx) + De^(-kx)](https://img.qammunity.org/2020/formulas/mathematics/high-school/fwizux5on8dpe7799t48f5q1s1f5irgnyk.png)
For
![Y(y)](https://img.qammunity.org/2020/formulas/mathematics/high-school/r7bdu809jnuhhteezj2uz6daou45aktbca.png)
![(d^2Y)/(dy^2) = -k^2Y(y)](https://img.qammunity.org/2020/formulas/mathematics/high-school/8kxberm957dd3vz4o5a3n3gnti9ndrxc7c.png)
Is the differential equation for a harmonic oscillator, so the solution is
![Y(y) = Acos(ky) + Bsin(ky)](https://img.qammunity.org/2020/formulas/mathematics/high-school/umc7u852tudnnkkz3hi9nqzjwpznhdidde.png)
Now, we evaluate the boundary conditions:
![u(x,0) = 0 \rightarrow Y(0) = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/xe0q55iee01qo8sr8a1r97hq1th0e60mhx.png)
![Y(0) = Acos(0) + Bsin(0) = 0; A = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/rfnsqccbd0sh5zl08sgpuxx4pznyizvwad.png)
![Y(y) = Bsin(ky)](https://img.qammunity.org/2020/formulas/mathematics/high-school/esfachireauz3sqftsjp3hbczy8veyh5h5.png)
The other
![u(x,b) = 0 \rightarrow Y(b) = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/6yjikuuxu9f42opdonx1z7t6lfyc1m677b.png)
![Y(b) = B\sin({kb}) = g(x); B = \frac{g(x)}{sin({kb})}](https://img.qammunity.org/2020/formulas/mathematics/high-school/69325i9x4xgytq2mxtl9ab2fzwdcymakgk.png)
![Y(y) = \frac{g(x)}{\sin({kb})} sin{(ky)}](https://img.qammunity.org/2020/formulas/mathematics/high-school/xs3271xp694g3mk3k9d35db1z6sj22khhl.png)
For
:
![u(0,y) = 0 \rightarrow X(0) =0](https://img.qammunity.org/2020/formulas/mathematics/high-school/ddfdrl072tk71o34wo9izw2ek8bfvumcpz.png)
![X(0) = Ee^(0) + De^(-0) =0; E+D=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/evjsd131ys6bdqcj7kmvg2kmgt0xqvuldk.png)
![E = -D](https://img.qammunity.org/2020/formulas/mathematics/high-school/b65yudyg2brsxf0l23uiltikhc5jpnqouu.png)
So,
![X(x) = E(e^(kx) - e^(-kx) ) = 2Esinh(kx) = Fsinh(kx))](https://img.qammunity.org/2020/formulas/mathematics/high-school/p03v6qz511vcyw2ldgc5rzta6db0i3lisi.png)
The other condition:
![u(a,y) = 0 \rightarrow X(a) = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/ys3bo7o1i19cf3fv76jkxx23w084293mhj.png)
![X(a) = F(sinh{(ka)}) = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/ay9u28dvnetlq52o5uueo0r7utjkns6reg.png)
So,
![u(x,t) = (g(x))/(sin((kb)))sin((ky)) Fsinh{(kx)}](https://img.qammunity.org/2020/formulas/mathematics/high-school/1ssmlcw4geja36p9khikh79b1zx2iiy3qw.png)